Autonomous control and trajectory tracking of quadrotor helicopter - Tianmiao Wang; Liewu Wang; Jianhong Liang; Yang Chen (2012 IEEE International Conference on Computer Science and Automation Engineering, 2012)
The research on autonomous miniature flying robots is intensified considerable owing to the increasing interest of unmanned aerial vehicle (UAV). This paper summarizes the nonlinear dynamics of a quadrotor helicopter and the measurements of the aerodynamic parameters of its propeller. We propose an attitude controller with the introduction of acceleration in error feedback, which will improve the stability and fast-tracking capability. In addition, a trajectory tracking controller is developed based on the along-track error and cross-track error feedback to track the waypoint. Finally, outdoor flight test results of attitude control and simple trajectory tracking are presented to verify the availability.